PEMBERDAYAAN ANAK MELALUI PROGRAM FAMILY BASED CARE DI SOS CHILDREN’S VILLAGE DI MEULABOH - Siti Hajar (Prodi Pengembangan Masyarakat Islam STAIN Teungku Dirundeng Meulaboh, 2022)
SOS Children's Village is a non-governmental social development organization, active in the field of children's rights and committed to helping the needs of children since 1949. Child empowerment focuses on family-based and long-term care for children who have lost family’s care and are neglected. with the aim of empowering children. Nurturing usually obtained from parents, for children who live in SOS Children's Village Meulaboh will receive nurturing from foster mothers and coaches. This research is a type of field research, the used method is descriptive qualitative using data obtained from interviews, observations and data from written documents related to this research. Based on the results of the study, it can be concluded that the empowerment of children in SOS Children's Village Meulaboh in the family based care program is the fulfillment of the fields of nurturing, education and child health through the stages and flow of SOS services. Supporting factors include the availability of adequate facilities and infrastructure, the presence of caregivers and coaches, the establishment of partnerships with several institutions or foundations, consistency from coaches, caregivers, and part timers. The inhibiting factors include the various backgrounds of the children in SOS, the constraints of part timers, the unavailability of facilities for gifted children in their areas of interest, as well as barriers from the children themselves who are less disciplined and less open to their environment.